2010
DOI: 10.1016/j.exer.2010.08.007
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 mediates surface contact between neutrophils and keratocytes following corneal epithelial abrasion in the mouse

Abstract: Corneal epithelial abrasion elicits an inflammatory response involving neutrophil (PMN) recruitment from the limbal vessels into the corneal stroma. These migrating PMNs make surface contact with collagen and stromal keratocytes. Using mice deficient in PMN integrin CD18, we previously showed that PMN contact with stromal keratocytes is CD18-dependent, while contact with collagen is CD18-independent. In the present study, we wished to extend these observations and determine if ICAM-1, a known ligand for CD18, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…After scratch injury alone (without infection), neutrophils recruited from the limbal vessels into the corneal stroma make ICAM-1-mediated surface contact with stromal keratinocytes, and ICAM-1 KO mice demonstrate decreased stromal infiltration (12). In P. aeruginosa keratitis after scratch injury, Hazlett and coworkers reported that ICAM-1-deficient mice had less-severe corneal opacities (as we observed) but similar neutrophil numbers and inflammatory cell infiltration on histopathology (17), which is different from our findings.…”
Section: Discussionmentioning
confidence: 99%
“…After scratch injury alone (without infection), neutrophils recruited from the limbal vessels into the corneal stroma make ICAM-1-mediated surface contact with stromal keratinocytes, and ICAM-1 KO mice demonstrate decreased stromal infiltration (12). In P. aeruginosa keratitis after scratch injury, Hazlett and coworkers reported that ICAM-1-deficient mice had less-severe corneal opacities (as we observed) but similar neutrophil numbers and inflammatory cell infiltration on histopathology (17), which is different from our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils 31 and NK cells 32 have been shown to play a role in corneal epithelium-wound healing, stromal remolding, and nerve regeneration. We next investigated whether their infiltrations were altered in DM healing corneas and the effects of IL-1Ra herein.…”
Section: Effects Of Il-1ra On the Infiltration Of Neutrophils And Nk mentioning
confidence: 99%
“…54 Neutrophils have been shown to act as an early response immune cells that play a key role in the healing of an epithelium-debridement wound. 31 A large number of NK cells infiltrate into the cornea and participate in the modulation of Figure 9 Schematic diagram deciphering the role of balanced IL-1beIL-1 receptor antagonist (IL-1Ra) signaling in mediating epithelial wound healing and its defects in the diabetic corneas. A: In the normal corneas, epithelium injury causes the release of alarmins (eg, high mobility group box 1 protein), which activates Toll-like receptors (TLRs), resulting in the initial induction of IL-1b and the secreted form of IL-1Ra (sIL-1Ra).…”
Section: Il-1ra and Diabetic Cornea Wound Healingmentioning
confidence: 99%
“…In the Aspergillus fumigates infected lung, CXCR2 recruits neutrophils to the infection site (Bonnett et al, 2006). In the cornea, ICAM-1, MIP-2 and other cytokines have a role in attracting neutrophils to the inflammatory site (Gagen et al, 2010;Zaidi et al, 2012;Tripathi et al, 2013). However, the regulator of neutrophil infiltration in FK is unknown.…”
Section: Introductionmentioning
confidence: 97%